2018
DOI: 10.1111/jade.12176
|View full text |Cite
|
Sign up to set email alerts
|

Aristotelian Appeals and the Role of Candidate‐Generated Videos in Talent Assessment

Abstract: Videos made by job candidates can be an effective means of promoting their qualifications, thus potentially helping them secure a job. However, little past research has focused on the impact of such videos on reviewers’ appraisals of a prospective candidate. Using Aristotle's means of persuasion as a methodological framework, this study first identified the most sought after candidate attributes identified by hiring firms, then explored the degree to which firm representatives felt two candidate‐generated vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Rhetoric theory is defined as the ability to see available means of persuasion in a particular case, which consists of the validity of arguments, characteristics of the speaker, and ability of emotions (Aristotle, 1991). The rhetoric theory is also particular in communication skills that can influence customers to purchase the product featured in the vWOM by conveying credible information to the customers (Huber & Pable, 2019). Each of the Rhetoric Theory components has a different meaning, which either refers to the information conveyed, the speaker, or the emotion of the speaker.…”
Section: Rhetoric Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Rhetoric theory is defined as the ability to see available means of persuasion in a particular case, which consists of the validity of arguments, characteristics of the speaker, and ability of emotions (Aristotle, 1991). The rhetoric theory is also particular in communication skills that can influence customers to purchase the product featured in the vWOM by conveying credible information to the customers (Huber & Pable, 2019). Each of the Rhetoric Theory components has a different meaning, which either refers to the information conveyed, the speaker, or the emotion of the speaker.…”
Section: Rhetoric Theorymentioning
confidence: 99%
“…(nonverbal messages) Expressed emotions and the similarities between the speaker and audiences (Huber and Pable, 2019).…”
Section: Pathosmentioning
confidence: 99%
“…Like many recent graduates, those in interior design often lack the benefit of experience and a well‐connected professional network. Regardless, some may be vying for positions against the likes of 30–75 similarly qualified candidates (Huber & Pable, ). Consequently, it behooves them to carefully consider any factors enhancing their employability and, in turn, determine how to convey desirable attributes early in the screening process.…”
Section: Literaturementioning
confidence: 99%
“…While literature lacks recent studies exploring the decision‐making processes of designers when making human capital decisions, studies have suggested that designers call on rapid information processes during the design process (Gray, Seifert, Yilmaz, Daly, & Gonzalez, ; Yilmaz & Seifert, ) and when reviewing information under time constraints (Huber, , , ). Given that over one in four of Huber and Pable's () hiring practitioner respondents received over 50 applicants for a typical entry‐level interior design job opening, one might infer that the time allocated to each candidate's package is relatively limited, and consequently, heuristics may factor heavily into these initial assessments.…”
Section: Literaturementioning
confidence: 99%